Trade Secret Protection Strategy Raising Awareness in the Business Sector - Humaera, Anaza Zahra; Yulinda, Tina (International Journal of Business, Law, and Education, 2025)
Trade secret protection is becoming increasingly important amidst intense business competition, especially in competitive sectors such as food and beverages. Information with economic value, such as marketing strategies and product formulas, is at risk of being leaked, which can cause financial and reputational damage to the company. Law No. 30 Year 2000 on Trade Secrets in Indonesia aims to protect such information, but many companies still struggle with its implementation. This research aims to develop guidelines for companies in drafting effective work agreements to protect trade secrets and examine the ethics and corporate social responsibility in maintaining confidentiality. The normative juridical method is used to analyze the existing legal framework and evaluate the effectiveness of the protection provided. It is hoped that the results of this study can contribute to the protection of trade secrets in Indonesia and increase companies' awareness of implementing the necessary measures to safeguard sensitive information.